PENGARUH KECERDASAN BUATAN DAN KEPUASAN PELANGGAN DALAM REKOMENDASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI E-COMMERCE - Rizma Adelia; Hani Hasanah; Laras Annisa Ulfitri Nedi (MANAJEMEN, 2025)
This study aims to analyze the influence of Artificial Intelligence (AI) and customer satisfaction in product recommendation systems on consumer purchasing decisions in e-commerce platforms.. This research employs a quantitative approach with purposive sampling, involving 160 respondents who have experienced AI-based product recommendations in e-commerce. Data were collected through online questionnaires and analyzed using smartpls 3. The results reveal that artificial intelligence significantly influences purchasing decisions on a partial basis. Likewise, customer satisfaction also shows a positive and significant effect. Simultaneously, both artificial intelligence and customer satisfaction have a significant impact on consumer purchasing decisions. These findings provide valuable implications for e-commerce platforms to develop more accurate, relevant, and user-centered recommendation systems.